Endosymbiont or host: who drove mitochondrial and plastid evolution? - Gross, Jeferson (BioMed Central, 2011)
The recognition that mitochondria and plastids are derived from alphaproteobacterial and cyanobacterial endosymbionts, respectively, was one of the greatest advances in modern evolutionary biology. Researchers have yet however to provide detailed cell biological descriptions of how these once free-living prokaryotes were transformed into intracellular organelles. A key area of study in this realm is elucidating the evolution of the molecular machines that control organelle protein topogenesis. Alcock et al. (Science 2010, 327 [5966]:649-650) suggest that evolutionary innovations that established the mitochondrial protein sorting system were driven by the alphaproteobacterial endosymbiont (an "insiders' perspective"). In contrast, here we argue that evolution of mitochondrial and plastid topogenesis may better be understood as an outcome of selective pressures acting on host cell chromosomes (the "outsiders' view"). REVIEWERS: This manuscript was reviewed by Gáspár Jékely, Martijn Huynen, and Purificación López-García.